2017
DOI: 10.1007/s00792-017-0954-y
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids from the extreme halophilic archaeon Haloterrigena turkmenica: identification and antioxidant activity

Abstract: Haloterrigena turkmenica was able to synthesize carotenoids when grown in halobacteria medium. These molecules have antioxidant properties and find application in food, cosmetic, and pharmaceutical fields. The carotenoids were extracted with methanol, separated by RP-HPLC, and identified by mass spectrometry and UV/Vis spectra analyses. The C carotenoids were the main pigments, and C, C, and C carotenoids were also detected. Seven geometric isomers were distinguished for bacterioruberin, monoanhydrobacteriorub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 39 publications
7
56
0
Order By: Relevance
“…Mass spectrometry provided the corresponding profiles for positively ionized fragments and their m/z for each major subfraction as shown in Figure 6 and Supplementary Figure S4, Supplementary Table S1. From the analysis of these spectroscopic and spectrophotometric data and comparison with previously reported information (Mandelli et al, 2012;Dina et al, 2017;Squillaci et al, 2017), it was inferred that Haloterrigena sp. strain SGH1 cells contain six C-50 molecules related to the BR family: four geometric isomers (5-cis-BR, 9-cis-BR, 13-cis-BR, and all-trans-BR) and two dehydrated derivatives (all-transtetra-anhydrous BR and cis-tetra-anhydrous BR) and, one the metabolic intermediate (all-trans-mono-anhydrous BR).…”
Section: Strain Sgh1mentioning
confidence: 64%
See 2 more Smart Citations
“…Mass spectrometry provided the corresponding profiles for positively ionized fragments and their m/z for each major subfraction as shown in Figure 6 and Supplementary Figure S4, Supplementary Table S1. From the analysis of these spectroscopic and spectrophotometric data and comparison with previously reported information (Mandelli et al, 2012;Dina et al, 2017;Squillaci et al, 2017), it was inferred that Haloterrigena sp. strain SGH1 cells contain six C-50 molecules related to the BR family: four geometric isomers (5-cis-BR, 9-cis-BR, 13-cis-BR, and all-trans-BR) and two dehydrated derivatives (all-transtetra-anhydrous BR and cis-tetra-anhydrous BR) and, one the metabolic intermediate (all-trans-mono-anhydrous BR).…”
Section: Strain Sgh1mentioning
confidence: 64%
“…strain SGH1 is a reversible, salt-dependent metabolic process and the maximum carotenoid content was obtained in cells grown at 25 • C and 25% NaCl. Comparatively, a lower carotenoid content has been registered for other halophilic archaea; e.g., 45 µg g −1 of dry biomass in Halococcus morrhuae (Mandelli et al, 2012), 75 µg g −1 of dry biomass in H. turkmenica (Squillaci et al, 2017) and 335 µg g −1 of dry biomass Haloarcula japonica (Yatsunami et al, 2014). Recently, Zalazar et al (2019) have reported that the bacterioruberin content (220 mg g −1 dry weight) in a hyperpigmented, genetically modified Haloferax volcanii strain HVLON3 is higher than in other haloarchaea.…”
Section: Bacterioruberin Biosynthesismentioning
confidence: 98%
See 1 more Smart Citation
“…Since the first publication on carotenoids from archaea in the early sixties (last century) [71,72] more than 850 works have been published in indexed journals about this subject (PUBMED: data of access December the 10th, 2019; 856 publications identify using "carotenoids" and "archaea" as keywords). Most of these works addressed the characterization of the pigments synthesized by archaea, mainly haloarchaea, some others look for potential applications (due to their high antioxidant capability) and more recently, several works describe molecular engineering to optimize de production of some pigments in order to upscale their production [73][74][75][76]. However, there is still controversy about the nature of the pathways for carotenogenesis in haloarchaea, and consequently, the production of overpigmented mutants as cell factories for carotenoid production is still a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The natural pigments most studied are the carotenoids, responsible for the yellow, orange, and red colors of some fruits, vegetables, flowers, fish, crustaceous, bacteria, and fungi [1]. The carotenoids production via biotechnology can be obtained by a diversity of microorganisms, such as bacteria [2], yeasts [3][4][5], microalgal [6], and filamentous fungi [7].…”
Section: Introductionmentioning
confidence: 99%